Open clusters and HII regions of our Galaxy - Obonyo, Willice Odhiambo (Department of Astronomy, 2016)
Open clusters are essential laboratories for understanding stellar evolution, as they allow constraints to be placed on stellar ages and luminosities. As distance indicators they are also important tracers of star formation in the Milky Way. One such cluster is Trumpler 27 that we identified for detailed study.The aim of the study is to estimate the distance, radial velocity, age, membership and reddening of the cluster using both spectroscopic and photometric techniques. We used new spectroscopic data collected from SAAO's 1.9m telescope together with existing photometric data from catalogues in the study of Trumpler 27. The spectra collected were classified using spectral atlases to determine the reddening in the field. Stars of the cluster were identified using selection techniques that made use of both infrared and optical Q parameters, spatial distribution and photometric techniques. The result from this work suggest that Trumpler 27 is made up of ~ 55 stars which are at different stages of evolution. The stars include main sequence stars, blue supergiants, two cool supergiants and maybe two WR stars.